EFEK PERLAKUAN KULIT BIJI BUNGA MATAHARI (Heliantthus annuus L) TERHADAP PRODUKSI BIOETANOL OLEH Saccharomyces cerevisiae - F.R. Wirandasari; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2014)
The research aimed of this study to sought determine effect pre-treatment of peel seeds, sunflower on bioethanol and fermentation efficiency in hydrolysis medium of peel sunflower seeds. The study was carried out experimentally using a completely randomized design. Skin pretreatment sunflower seeds on the production of bioethanol by Saccharomyces cerevisiae consists of pre-treatment controls, in stream for 3 hours at 1210C, hydrolysis H2SO4 and NaOH hydrolysis. The result of this study should pre-treatment have (P<0,05) effect of bioethanol production. Key words: Saccharomyces cerevisiae, Bioethanol, Nitrogen, Carbon, Leather Sunflower Seed (Helianthus annuus L), fermentation efficiency